Research on Microgrid Control System with Different DG Types - Litao Wang; Weihua Tian; Baixiang Zheng (Dianxin kexue)
According to the grid-connected and islanded operating modes of microgrid and the changeover between them,a control strategy of microgrid with different kinds of DG（distributed generation）was proposed,which monitors the operating states of both microgrid and power network and provides the unified coordinating control by the central controller of microgrid. DC micro-grid and AC micro-grid hybrid was adopted. An independent public DC/AC converter used in AC side. Not only the load demand was satisfied, but also the converter resources were saved. P/Q control model was established based on grid-connected model. And in isolated mode, the converter was working in V/f control. The direct-drive permanent magnet wind power generation system, dual-stage PV generation system and Li-ion battery energy storage system were used as networking unit, and the results of transferring microgrid operation, modes and cutting or increasing load in islanded mode show the effectiveness and feasibility of the proposed control strategies.